Identification of Parasites in Snakehead Fish (Channa striata) in Meunasah Manyang Village Lhoknga Subdistrict Aceh Besar - Adil Umara; Muttaqien Bakri; Muhammad Hambal (Jurnal Medika Veterinaria, 2014)
The study aimed at identifying the types of parasites that infect snakehead (C. striata) fish as well as to determine the prevalence of the parasite species. A total of 51 snakehead fish was captured using nets and traps then examined at Parasitology Laboratory of Veterinary Medicine Faculty Syiah Kuala University Banda Aceh. Ectoparasites inspection was done by observation of the outer body organs as well as by making the mucus smear examined under a microscope, while endoparasites inspection was done by observation on the surface of the digestive tract and heart, and also thin and thick boold smear. The study revealed that two types of parasites that infect snakehead fish in irrigation Cot Balee were Pallisentis nagpurensis and Trichodina spp. It also found larvae obtained from the intestinal villi scrapings that have not been identified. A total of 96% snakehead fish infected by P. nagpurensis, 6% infested with Trichodina spp., and 10% infested by unidentified larvae.Key words: parasite, snakehead fish (Channa striata), Palllisentis nagpurensis, Trichodina spp, prevalence